Analytical and experimental investigations into material removal mechanism of abrasive jet precision finishing with grinding wheel as restraint. (1st January 2012) - Li, Changhe; Liu, Zhanrui; Hou, Yali; Ding, Yucheng
The material removal mechanism of abrasive jet precision finishing with grinding wheel as restraint was investigated based on the size ratio of the characteristic particle size to the film thickness between a grinding wheel and a workpiece. The single abrasive movement characteristic was studied under the two-body lapping and three-body machining modes. The critical condition for the transformation from two-body lapping to three-body polishing was analysed. Experiments were conducted for theoretical model verification, and the experimental results showed that the surface roughness value decreased with the increase of the number of cycles. Furthermore, as the micrographs show, the machined surface changed from directionally continuous micro-grooves to random pits as machining progressed. The average spacing of finished surface profile waviness was decreased and the ripples and peak density were increased. It was found that the theoretical analysis is accordant with the experimental results.